Different versions of assessment for learning in the subject of physical education - Tolgfors, Björn (Physical education and sport pedagogy, 2018)
Background: Assessment for learning (AfL) is now marketed across the Western world as a key to an improved goal attainment in most school subjects. The concept has also attracted increased interest in the international research field of physical education (PE) in recent years. According to (Chan, K., P. J. Hay, and R. Tinning. 2011. "Understanding the Pedagogic Discourse of Assessment in Physical Education." Asia-Pacific Journal of Health, Sport and Physical Education 2 (1): 3-18) assessment both influences the teaching and learning process and defines its product, which is referred to as the 'backwash effect'. Contrasting versions of AfL will therefore have different consequences, regarding the constitution of teacher and student subjectivities as well as characteristics of the subject content. These consequences can be understood in terms of didactics, which in a European research tradition focuses on the relationship between teacher, student and subject content (Hudson, B., and M. A. Meyer, eds. 2011. Beyond Fragmentation: Didactics, Learning and Teaching in Europe. Opladen and Farmington Hills: Barbara Budrich Publishers). Purpose and research question: The purpose of the study is to identify teacher and student subjectivities as well as subject content, constituted through different versions of AfL in school PE. The identification of the different versions of AfL and the relations established through each of them is facilitated by the research question: 'What is performed and produced in the formative assessment practice of PE?' The findings are then discussed on the basis of the question: 'Assessment for what learning?' Methods: In order to answer the research question, a mixed method of lesson observations and semi-structured interviews was used (cf. Patton, M. Q. 2002. Qualitative Research and Evaluation Methods. 3rd ed. Thousand Oaks, California: Sage Publications Inc). Thirteen PE lessons were observed at two different upper secondary schools, involving four classes attaining both vocational and pre-university programmes. Semi-structured interviews were conducted with 17 of the students and their two male PE teachers. The empirical material consisted of field notes and transcriptions of the interviews, with an emphasis on the latter. In the first step of the analysis the material was categorised by means of the five key strategies of AfL (Wiliam, D. 2011. "What is Assessment for Learning?" Studies in Educational Evaluation 37: 3-14. Elsevier), in order to identify different ways of realising the concept in the subject of PE. The second step was a combination of a performativity (Ball, S. J. 2003. "The Teacher's Soul and the Terrors of Performativity." Journal of Education Policy 18 (2): 215-228) and a didactic (Hudson, B. 2002. "Holding Complexity and Searching for Meaning: Teaching as Reflective Practice." Journal of Curriculum Studies 34 (1): 43-57) analysis, which clarified the relations established under different circumstances in the formative assessment practice. Findings: The findings highlight five versions of AfL in PE, named after their most prominent features or functions, AfL as: (i) Empowerment, (ii) Physical Activation, (iii) Constructive Alignment, (iv) Grade Generation, (v) Negotiation. 'Among the products of discursive practices are the very persons who engage in them' (Davies, B., and R. Harré. 2001. "Positioning: The Discursive Production of Selves." In Discourse Theory and Practice, edited by M. Wetherell, S. Taylor, and S. J. Yates. London: Sage, 263). Accordingly, different teacher and student subjectivities as well as characteristics of the subject content are constituted in each of these fabrications. Conclusions: The so-called 'backwash effect' (Torrance, H. 2012. "Formative Assessment at the Crossroads: Conformative, Deformative and Transformative Assessment." Oxford Review of Education 38 (3): 323-342. London: Routledge) implies that the contrasting versions of AfL promote different kinds of learning, such as: (i) increased autonomy, (ii) participation in a community of practice, (iii) acquisition of prescribed abilities, (iv) criteria compliance, (v) group development. However, the big idea of AfL is to adapt the teaching to the students and not the students to the standards.